2020
DOI: 10.7759/cureus.8428
|View full text |Cite
|
Sign up to set email alerts
|

Weil's Disease: A Rare Cause of Jaundice

Abstract: Weil's disease is a complication of untreated leptospirosis and can be fatal. Awareness of leptospirosis and its hepatic manifestations are limited. We report the case of a 50-year-old man with gastrointestinal symptoms and a cholestatic pattern of liver injury diagnosed with Weil's disease. The patient showed remarkable improvement after treatment with appropriate antibiotics with normalization of liver function in one month. This case highlights the importance of recognizing leptospirosis and its myriad pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…The abdominal pain may be secondary to acalculous cholecystitis and/or pancreatitis. The presence of jaundice demonstrates a poor prognosis with a mortality of 19.1% [ 4 ]. Most cases of leptospirosis-induced pancreatitis are self-limiting and will resolve.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The abdominal pain may be secondary to acalculous cholecystitis and/or pancreatitis. The presence of jaundice demonstrates a poor prognosis with a mortality of 19.1% [ 4 ]. Most cases of leptospirosis-induced pancreatitis are self-limiting and will resolve.…”
Section: Discussionmentioning
confidence: 99%
“…It has the potential to be fatal in some cases; in autopsy reports, specimens have shown congested sinusoids and distension of the space of Disse, which is located between the sinusoids and hepatocytes [ 3 ]. It is important to monitor these patients closely as they can develop fulminant liver failure [ 4 ]. Shintaku et al [ 6 ] reported a case where an autopsy showed severe damage in zone 3 (centrilobular region) and evidence of extreme necrosis of the hepatocytes with extensive hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Documented to last for up to 30 days, the immune phase typically begins from 7–10 days after the first onset of symptoms [ 36 ]. Satiya et al [ 160 ] emphasized that untreated leptospirosis can lead to fatal hepatic manifestations, such as jaundice. Liver failure, kidney failure and respiratory shock are also notable complications of severe leptospirosis.…”
Section: Transmission and Pathogenesismentioning
confidence: 99%
“…Despite ongoing research efforts, the pathophysiological mechanism of leptospirosis remains poorly understood. However, it is theorized that this disease occurs as a result of the host immune response towards the organisms, which by now should be excessively abundant in the blood, liver, lungs, kidneys, cerebrospinal fluid and the aqueous humour among other organs [ 160 ]. As leptospires bind to host cells, cytokines (interleukin-6, interleukin-10 and TNF-α) and antimicrobial peptides (AMPs) are released to limit the invasive damages incurred by the bacteria.…”
Section: Transmission and Pathogenesismentioning
confidence: 99%